Higher dominant muscle strength is mediated by motor unit discharge rates and proportion of common synaptic inputs - Edoardo Lecce; Alessandro Del Vecchio; Stefano Nuccio; Francesco Felici; Ilenia Bazzucchi (Scientific Reports)
Abstract Neural determinants explaining the asymmetrical force and skill observed in limb dominance still need to be comprehensively investigated. To address this gap, we recorded myoelectrical activity from biceps brachii using high-density surface electromyography in twenty participants, identifying the maximal voluntary force (MVF) and performing isometric ramp contractions at 35% and 70%MVF and sustained contractions at 10%MVF. Motor unit discharge characteristics were assessed during ramp contractions, the proportion of common synaptic input to motoneurons was calculated with coherence analysis, and the firing rate hysteresis (∆F) was used to estimate spinal motoneuron intrinsic properties. The dominant limbs presented a greater MVF compared to the non-dominant side (+ 9%, p = 0.001), with similar relative recruitment and derecruitment thresholds of motor units (p > 0.05). The discharge rate was significantly higher on the dominant side (p < 0.001), along with a greater proportion of common synaptic input (+ 14%, p = 0.002). No significant differences were observed in the ∆F (p > 0.05). Our findings suggest that greater strength on the dominant side is associated with higher neural drive to muscles due to a greater proportion of common synaptic inputs rather than differences in motoneuron intrinsic properties. These results underscore neural asymmetries at the motor unit level, corresponding to different mechanical outputs underlying limb dominance.